2019
DOI: 10.1155/2019/2623161
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Function in Fibromyalgia: A Study by Functional Near-Infrared Spectroscopy

Abstract: Previous studies indicated changes of motor cortex excitability in fibromyalgia (FM) patients and the positive results of transcranial stimulation techniques. The present study aimed to explore the metabolism of motor cortex in FM patients, in resting state and during slow and fast finger tapping, using functional Near-Infrared Spectroscopy (fNIRS), an optical method which detects in real time the metabolism changes in the cortical tissue. We studied 24 FM patients and 24 healthy subjects. We found a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 36 publications
(43 reference statements)
3
33
0
Order By: Relevance
“…The main results of the present study partly confirmed previous findings [21]. Patients suffering from FM had a reduced motor performance as tested by finger tapping task, and a reduced tone of cortical motor areas, especially evident during fast movement.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The main results of the present study partly confirmed previous findings [21]. Patients suffering from FM had a reduced motor performance as tested by finger tapping task, and a reduced tone of cortical motor areas, especially evident during fast movement.…”
Section: Discussionsupporting
confidence: 92%
“…We did not observe a compensatory activity of right hemisphere in FM patients, as generally occurs in unilateral motor cortex dysfunction [47] The hypometabolism here observed in FM patients could involve the bilateral cortical motor areas, with an absence of contralateral compensation during simple unilateral motor activities. We can assume that the activation levels of the motor cortex were independent of the velocity of the finger tapping task, as, in line with our previous study [21], we did not find any relevant correlation between the motor speed and haemodynamic responses either in patients or in controls. The results of haemodynamic responses suggest that FM patients could have a dysfunction in supplementary and primary motor cortex modulation.…”
Section: Reduced Motor Performance and Motor Cortical Areas Activatiosupporting
confidence: 91%
See 2 more Smart Citations
“…The inter-stimulus interval was fixed at 10 s. For each participant, we evaluated the subjective pain threshold according to the method of the limits, and we delivered laser stimuli when the subjects felt a pinprick sensation [17]. The experimenter asked each participant to rate his/her pain on a numerical rating scale (NRS) [18]. After each laser stimulation, the subjects were required to rate the perceived intensity of their pain on the visual analogue scale (VAS) [19].…”
Section: Eeg Recordingmentioning
confidence: 99%